Spin-dependent edge detection and imaging enabled by optical circularly polarised states - Jiale Chen; Zhao-xian Chen; Zi-xin Zhou; Yan-qing Lu; Jun-long Kou (Light: Advanced Manufacturing)
In photonic crystal slab (PCS) structures, the bound states in the continuum (BICs) and circularly polarised states (dubbed C-points) are critical topological polarisation singularities in momentum space that have garnered significant attention owing to their novel topological and optical properties. In this study, we engineered a novel PCS imager featuring two C-points with opposite chirality through symmetry breaking, resulting in maximal asymmetric transmission responses characterised by near-unity circular dichroism (CD) values. By harnessing the chiral selectivity of the C-points, a high-CD PCS imager can provide two sets of optical transfer functions (OTFs) to facilitate both edge detection and bright-field imaging. Notably, one set of OTFs was finely tuned to a Lorentzian line shape to achieve perfect edge detection. We developed a multifunctional imaging system by integrating a PCS imager into a traditional optical system. Both theoretical and experimental demonstrations confirmed that this system provides bright-field and edge-enhanced images with micrometer-scale resolution. Furthermore, these two independent functions can be easily switched by altering the circular polarisation state of the light source.